Obesity and breast cancer - A. I. Berishvili; A. G. Kedrova; T. A. Greyan; O. V. Zaitseva (Опухоли женской репродуктивной системы, 2022)
The paper presents an analysis of the latest literature data on the problem of obesity and breast cancer (BC). This review presents modern approaches to the diagnosis of BC in obese patients, new molecular methods of breast imaging,  analyzes the features of the course of BC with obesity depending on menstrual status, molecular biological subtypes of the tumor, the mechanisms of the development of BC against the background of obesity.